1998
DOI: 10.1002/(sici)1097-024x(19980410)28:4<347::aid-spe145>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of test set minimization on fault detection effectiveness

Abstract: Given a test set T to test a program P, there are at least two attributes of T that determine its fault detection effectiveness. One attribute is the size of T measured as the number of test cases in T. Another attribute is the code coverage measured when P is executed on all elements of T. The fault detection effectiveness of T is the ratio of the number of faults guaranteed to result in program failure when P is executed on T to the total number of faults present in P. An empirical study was conducted to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
129
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(140 citation statements)
references
References 14 publications
6
129
3
Order By: Relevance
“…Related work in the context of test suite reduction can be classified into two main categories: The works in which a new technique is presented [3,4,5,16,9,6,7], and empirical studies on the previous techniques [1,2,15,17]. The works which propose a new approach commonly include heuristic algorithms [14], genetic algorithm-based techniques [18] and approaches based on integer linear programming [19].…”
Section: Test Suite Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related work in the context of test suite reduction can be classified into two main categories: The works in which a new technique is presented [3,4,5,16,9,6,7], and empirical studies on the previous techniques [1,2,15,17]. The works which propose a new approach commonly include heuristic algorithms [14], genetic algorithm-based techniques [18] and approaches based on integer linear programming [19].…”
Section: Test Suite Reductionmentioning
confidence: 99%
“…In previous empirical studies [15] researchers commonly apply various code coverage criteria in their reduction techniques. The results of empirical studies [2,17] show that the more percentage of the test suite size is reduced the more percentage of faults will be lost.…”
Section: Test Suite Reductionmentioning
confidence: 99%
“…In an early study, Wong et al address the question of the effect on fault detection of reducing the size of a test set while holding coverage constant (Wong et al, 1997(Wong et al, , 1998. Their experiments were carried out over a set of commonly used UNIX utilities implemented in C. These programs were manually seeded with faults, producing variant programs each of which contained a single fault.…”
Section: Previous Test-reduction Experimentsmentioning
confidence: 99%
“…The effect on the fault finding capability of the reduced test-suites is, however, unclear and the studies show conflicting evidence. Wong et al (1997Wong et al ( , 1998 found no significant effect in fault finding ability between the full suites and the reduced suites. On the other hand, Rothermel et al (1998) and Jones and Harrold (2003) showed that the reduced test-suites can be dramatically worse with respect to fault finding.…”
mentioning
confidence: 90%
See 1 more Smart Citation